Production Design for "Sunting" Palembang Accessories in Tanjung Batu District, Ogan Ilir Regency - Erlison, Melati; Hasan, Hasan (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This study has a formulation and objectives, namely: How is the production design for making Palembang editing accessories in Tanjung Batu District, Ogan Ilir Regency, and aims to describe the results of the process of making Palembang editing accessories at the Aswar Syarif outlet. The research method used is a qualitative descriptive analysis based on the philosophy of positivism with data collection techniques: observation, interviews, and documentation and data analysis using the Miles and Huberman technique, consisting of: data reduction, data display, and conclusion drawing/verification. The results of the study indicate that there are five stages of the process in the process of making production design Palembang edit. 1. The stage of determining tools and materials (the stage of determining the use of tools and materials to be used in making accessories), 2. The stage of forming the basic pattern of accessories (the most basic stage of making crown patterns using mall base materials, 3. Sculpting patterns on copper-based materials (in this stage the craftsmen use chisels to carve or form carvings on accessories), 4. Tidying up the details of the shape of accessories (this stage re-arranges the shapes and motifs that have been made using tools such as pliers and then enters the finishing or coloring stage), 5. The finishing stage or the finishing stage and the coloring stage (this stage the refinement or finishing stage and the edit coloring stage are cleaned using a special liquid so that the color on the edit accessories or crown lasts a long time.